Ponzi's scheme the true story of a financial legend - Zuckoff, Mitchell (Random House, 2005)
It was a time when anything seemed possible, and for a few weeks in 1920, Charles Ponzi made it all come true. Promising to double investors' money in three months, the dapper, charming Ponzi raised the "rob Peter to pay Paul" scam to an art form. Ponzi was a likable man. His intentions were noble, his manners impeccable, his sales pitch enchanting. Born to a genteel Italian family, he immigrated to the United States with big dreams but no money. Only after he fell hopelessly in love did Ponzi light on the means to make his dreams come true. At the peak of his success, he was taking in more than
Keywords: Ponzi, Charles; Ponzi, Charles -- 1883-1949; Geschichte; Commercial crimes -- United States -- Case studies; Ponzi schemes -- United States -- History; Swindlers and swindling -- Biography; Swindlers and swindling -- United States -- Biography; USA; Biografie; Fallstudiensammlung